Pyroptosis-Related Signature Predicts the Progression of Ulcerative Colitis and Colitis-Associated Colorectal Cancer as well as the Anti-TNF Therapeutic Response - Yumei Ning; Kun Lin; Jun Fang; Xiaojia Chen; Xinyi Hu; Lan Liu; Qiu Zhao; Haizhou Wang; Fan Wang (Journal of Immunology Research)
Ulcerative colitis (UC) is a complex intestinal inflammation with an increasing risk of colitis-associated colorectal cancer (CAC). However, the pathogenesis is still unclear between active UC and inactive UC. Recently, it has been reported that pyroptosis-related genes (PRGs) are closely associated with inflammatory disease activity. Nevertheless, the specific roles of PRGs in the progression and treatment of UC and CAC remain unclear. In this study, we identified 30 differentially expressed PRGs based on the immune landscape of active and inactive UC samples. Meanwhile, weighted gene coexpression network analysis was applied to explore important genes associated with active UC. By intersecting with the differentially expressed PRGs, CASP5, GBP1, GZMB, IL1B, and IRF1 were selected as key PRGs to construct a pyroptosis-related signature (PR-signature). Then, logistic regression analysis was performed to validate the PR-signature and establish a pyroptosis-related score (PR-Score). We demonstrated that PR-Score had a powerful ability to distinguish active UC from inactive UC in multiple datasets. Besides, PR-Score was positively correlated with immune cell infiltration and inflammatory microenvironment in UC. Lower PR-Score was associated with a better response to anti-TNF therapy for patients with UC. Additionally, high-PR-Score was found to suppress CAC and improve the survival outcomes of patients with colorectal cancer. Finally, the levels of the PR-signature genes were validated both in vitro and in vivo. These findings can improve our understanding of PRGs in UC and provide new markers for predicting the occurrence of active UC or CAC and the treatment of UC.